Novel signatures for vector-like quarks - Aguilar Saavedra, J. A. (2017)
We consider supersymmetric extensions of the standard model with a vector-like doublet (T B) of quarks with charge 2/3 and −1/3, respectively. Compared to non-supersymmetric models, there is a variety of new decay modes for the vector-like quarks, involving the extra scalars present in supersymmetry. The importance of these new modes, yielding multi-top, multi-bottom and also multi-Higgs signals, is highlighted by the analysis of several benchmark scenarios. We show how the triangles commonly used to represent the branching ratios of the ‘standard’ decay modes of the vector-like quarks involving W, Z or Higgs bosons can be generalised to include additional channels. We give an example by recasting the limits of a recent heavy quark search for this more general case.